The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1542/peds.2005-0259
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in Survival of People With Cerebral Palsy in the United Kingdom

Abstract: Objectives. Regional variation in survival of people who have cerebral palsy (CP) has been observed but not previously investigated in detail. In addition to true differences, variations in the methods and definitions used, completeness of ascertainment, and the role of potential confounding factors all have been proposed as possible explanations for these observed variations. Our aim was to assess the regional differences in survival of young people with CP and the effect on survival of socioeconomic differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 17 publications
2
62
0
Order By: Relevance
“…Hutton et al 4 found no birth cohort effect for children of normal birthweight but some effect for low birthweight. Hemming et al 3 reported 'no evidence of any secular changes in survival'. Further, although only indirectly relevant to CP, recent work on individuals with spinal cord injury 9 indicates that the improvements in survival are largely confined to the critical first few years after injury.…”
Section: Secular Trends: Past and Futurementioning
confidence: 98%
See 3 more Smart Citations
“…Hutton et al 4 found no birth cohort effect for children of normal birthweight but some effect for low birthweight. Hemming et al 3 reported 'no evidence of any secular changes in survival'. Further, although only indirectly relevant to CP, recent work on individuals with spinal cord injury 9 indicates that the improvements in survival are largely confined to the critical first few years after injury.…”
Section: Secular Trends: Past and Futurementioning
confidence: 98%
“…13 The study also noted comparability of estimates from the California and the UK. Figure 1 compares survival of children with severe disabilities in the California database and the 2005 study of Hemming et al 3 The survival curve from the Hemming et al 3 study is for children with 'four severe disabilities'. These are with respect to ambulation, cognitive function, hand use, and visual function.…”
Section: Comparisons Between Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mortality rates are higher, and survival probabilities lower, for those with more severe CP, severity being measured by simple functional variables including gross and fine motor skills (ambulation, rolling, or crawling) and feeding ability. [12][13][14][15][16] Comparisons of survival rates in persons with CP in the USA, the UK, and Australia that have accounted for these basic functional vari- The purpose of the present study was to determine whether ongoing management of hypertonia with ITB is associated with an increase in the long-term risk of mortality in persons with CP. …”
mentioning
confidence: 99%